9514 1404 393
Answer:
x^2 +4x -21
Step-by-step explanation:
Substitute the given expressions and simplify.
f(x) + g(x)
= (x^2 +3x -28) +(x +7)
= x^2 +(3+1)x +(-28 +7)
= x^2 +4x -21
Answer:
This is verry easy! Is 105.56,do u need expabation?
Answer:
69
Step-by-step explanation:
(x+54+57)=180
x=69
Answer:
about 3 seconds
Step-by-step explanation:
hope this helps
Answer:
2
Step-by-step explanation:
2 (x-2)=8 equal to 2x-4=8, put -4 to the other side by subtracting 4 on both sides once you do you get 2x=4 so 4 divided by 2 equals 2.